Covalent Organic Frameworks as Electrode Materials for Metal Ion Batteries: A Current Review. Issue 10 (3rd September 2020) - Wang, Zhaolei; Jin, Weize; Huang, Xiaoyu; Lu, Guolin; Li, Yongjun
Abstract: As the world moves toward electromobility, our daily lives are flooded with variety of lithium ion batteries (LIBs), and the concerns of cost, safety and environmental friendliness of LIBs spring up in the minds of scientists. Although organic electrodes have been considered as promising alternatives to their inorganic counterparts, some intrinsic weaknesses still plague scientists, such as high solubility, low conductivity and sluggish ion diffusion. The emergence of covalent organic frameworks (COFs) attracts our attention because of their robust networks and open pores that could facilitate the infiltration of electrolyte ions when used as electrodes for metal‐ion batteries (MIBs). In this review, we summarized the recent progress of COFs as electrode materials, and the strategies toward enhancing electrochemical performance of COF‐based electrode in MIBs are discussed. Hopefully, this review will provide a fundamental guidance for future development of COF‐based electrodes. Abstract : Covalent organic frameworks (COFs) have attracted extensive attention owing to their robust network enhanced stability and open pores that could facilitate the infiltration of electrolyte ions when used as electrode materials for metal‐ion batteries (MIBs). In this review, we have summarized recent progresses of COFs as electrode materials in various MIBs, and then discussed the strategies toward enhancing electrochemical performance (capacity and rate performance) of COF‐based electrode in MIBs.